Peningkatan Hasil Belajar Siswa Dengan Model Think Pair Share (TPS) Berbantuan Mystery Pics - Renanda Wahyu Wardana; Lovika Ardana Riswari; Lintang Kironoratri (WASIS : Jurnal Ilmiah Pendidikan, 2023)
The research aims to improve student learning outcomes by applying the Think Pair Share model assisted by Mystery Pics for fourth grade students at SD 2 Hadipolo.The research used is classroom action research. This research was conducted in 2 cycles with each cycle consisting of planning, action, observation, and evaluation. This research was conducted at SD 2 Hadipolo. The subjects used were Grade IV SD 2 Hadipolo students for the 2022/2023 academic year, with a total of 19 students, consisting of 13 male students and 6 female students. Data collection techniques carried out in this study include observation and tests. The instrument used to measure learning outcomes in this study is a matter of evaluation. The data in this study were analyzed in a quantitative descriptive manner.The results of this study note that the percentage of students in the skill of writing Pancasila precepts questions is 56% with category D for the qualification of completeness needing guidance. In cycle II there was an increase compared to cycle I in writing Pancasila precept questions by 91% with category B for good thoroughness qualifications.